Persistent trophoblastic tumors - M. N. Tikhonovskaya; D. A. Bystritskaya; V. V. Kuznetsov; L. A. Meshcheryakova (ABV-press, 2014)
Persistent trophoblastic tumors (PTT) are the most common trofhoblastic tumors, which develop in women when proliferative trophoblastic activ- ity remains after evacuation of hydatidiform mole. The term persistent trophoblastic disease (PTD) is also widely used in the world literature. When PTD develops, new tissue is often not obtained. PTD is defined as a plateau or rise of serum β-hCG concentrations in tree subsequent weekly blood samples for 2 consecutive weeks (1, 8, 15 measurement days), the detection of β-hCG rise 6 months after hydatidiform mole evacu- ation. β-hCG is a glycoprotein hormone produced by trophoblastic tissue and a key tumor marker of gestational trophoblastic disease (GTD) with almost 100 % sensitivity and specificity. A persistent trophoblastic tumor may have the histological features of invasive hydatidiform mole, cho- riocarcinoma or rare forms of trophoblastic disease. PTD is a fatal disease, which occurs in women of reproductive age. PTT is nowadays typi- cally treated with chemotherapy according to international standards for GTD management. In the case of early identification and adequate treatment of PTT the cure rates approach 100 %.